2010
DOI: 10.1111/j.1365-2214.2010.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Adoption and attachment theory’ the attachment models of adoptive mothers and the revision of attachment patterns of their late-adopted children

Abstract: Our data suggest that revision of the attachment patterns in the late-adopted children is possible but gradual, and that the adoptive mothers' attachment security makes it more likely to occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
(30 reference statements)
0
37
1
Order By: Relevance
“…In the SRP, the child experiences two separations from the mother and two reunions with her, both of which are coded. The first separation lasts for 10-15 minutes, the second for approximately 45-60 minutes (Pace & Zavattini, 2011). The first coding comprises assigning scores on two scales: avoidance and security.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SRP, the child experiences two separations from the mother and two reunions with her, both of which are coded. The first separation lasts for 10-15 minutes, the second for approximately 45-60 minutes (Pace & Zavattini, 2011). The first coding comprises assigning scores on two scales: avoidance and security.…”
Section: Methodsmentioning
confidence: 99%
“…Globally adoption research, on the one hand, has pointed out that late-adopted children are at high risk for elevated rates of socio-emotional and behavioural difficulties, including insecure/disorganized attachment patterns and internalizing and externalizing behaviour problems; on the other hand, high resilience, capacity of recovery from early deprivation, ability to build positive representations of new caregivers, and earned attachment security emerged in adopted children and their adoptive families (Barone & Lionetti, 2012;Bimmel, Juffer, van IJzendoorn, & Bakermans-Kranenburg, 2003;Pace & Zavattini, 2011;Pace, Cavanna, Velotti, & Zavattini, 2014;. Recent longitudinal attachmentbased studies on adoption and maternal sensitivity showed that more sensitive parenting -in infancy middle childhood, and/or adolescence-predicted continuity of secure attachment of adopted children from infancy to adolescence, less inhibited and delinquent behaviours in adolescence and secure attachment representations in young adulthood (Beijersbergen, Juffer, Bakermans-Kranenburg, & van IJzendoorn, 2012;Pace, Di Folco, Guerriero, Santona, & Terrone, 2015a;Schoenmaker et al, 2015a; IJzendoorn, 2013;van der Voort et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The prospect for attachment revision has been realised in this population, as earlier attested, by a growing body of research involving maltreated children who have been both fostered and adopted from State care (Dozier, Stovall, Albus, & Bates, 2001;Pace & Zavattini, 2011). Notable from these studies are the positive shifts found in a child's relational expectancies when placed with caregivers assessed as attachment secure (Pace & Zavattini, 2011;Steele et al, 2010).…”
Section: Original Articlementioning
confidence: 97%
“…A growing number of attachment researchers have found that the internal working model of a child's new caregivers, with respect to attachment, is an important element in the revision of the child's internal working model of relationships (Pace & Zavattini, 2011). Thus, care practice social workers need to pay close attention to relational facets in prospective caregivers' assessments as some literature suggests that practitioners struggle to understand the role attachment orientation plays in the care relationship (Bick & Dozier, 2008).…”
Section: Findings and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation